Penerapan Ayat Takwil Dalam Surah Taha Ayat 5 Untuk Menanamkan Religiusitas Mahasiswa UINSU Prodi Pendidikan Bahasa Arab II Stambuk 2020 - Alima Rizkia Hsb; Dedi Masri; Muhammad Alfiyansah; Nur Azizah Hrp; Fauzan Azima (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
This study explains the application of the Takwil verse in surah Taha verse 5 to instill the religiosity of students at the State Islamic University of North Sumatra Medan Arabic Language Education Study Program II Stambuk 2020. The type of research in this paper is qualitative research. Data collection techniques used by way of interviews and also with various sources in the form of books and journals. The results of this study indicate that what must be instilled and applied in the student environment is that the understanding of surah Taha verse 5 is that Allah exists without a place. And the value of religiosity found in it is related to the issue of aqidah and about the nature of God which is different from the nature of creatures.